E-017 Intracranial Stenting with Balloon Mounted Stents: Initial Safety and Long Term Follow up. (14th July 2013) - Evans, A; Geraughty, S; Gaughen, J; Jensen, L; Wintermark, M
Abstract : Introduction: The SAMMPRIS trial demonstrated that intracranial stenting for symptomatic intracranial stenosis ICS (70-99%) with the Wingspan system is significantly more dangerous than best medical management with a 30 day stroke or death rate of 12.5 % for stenting vs 5.3 % for medical management. Deployment of the Wingspan stent is a complicated four step procedure, including an exchange procedure. In contrast, the balloon mounted coronary stent (BMCS) is a single step process without the need for an exchange procedure. Based on our single centre experience, we hypothesise that intracranial stenting with BMCS is a less complicated, clinically viable alternative for patients with symptomatic ICS who fail best medical therapy. Methods: We performed a retrospective chart review of all patients at our centre with symptomatic ICS (defined as >70%) and attempted placement of BMCS (n=39) between 12/2005-6/2012. The review was independent and conducted by members of the department of neurology, not members of the treatment team. Pretreatment ICS was measured by conventional cerebral angiography in all cases. Clinical outcomes included peri-procedural stroke or death prior to hospital discharge and all cause stroke or mortality within serial follow-up. Procedural outcomes included complications of stent placement and long-term stent patency. Follow-up was available up to 72 months with a mean follow-up of 21.8 months. Clinical outcomes were independently adjudicated by a stroke neurologist. Pre-treatment and follow-up angiography was adjudicated by an independent diagnostic neuroradiologist. Following the procedure, all patients are treated with combination aspirin 325 mg for life and clopidogrel for 90 days following stent placement. Results: BMCS was attempted in 39 patients (15 women, 24 men; age range 30–80 years, mean 60.8 years). The technical success rate for the procedure was 95%. None of the patients who were treated for stenosis of the anterior circulation suffered a neurologic event. Four patients treated for posterior circulation stenosis suffered small peri-procedural infarcts. (2 basilar, 2 vertebral) None of the infarcts were haemorrhagic in nature. There were no periprocedural deaths. Clinical and angiographic follow up was available in 35 of the 39 patients. Beyond 30 days there were no stroke related deaths. Two late infarcts occurred. In one case the infarct occurred in the left MCA territory five months after placement of a left ICA stent. In the second case, the patient suffered a small right insular territory infarct three months following right MCA stent placement. In both cases angiograms revealed that the stents were patent. Thirty one of the thirty five patients available for follow up had no significant restenosis with an average follow up time of 25 months. There was one asymptomatic stent occlusion seen on 3 months follow-up. Three patients were successfully treated for restenosis. Conclusion: This small single centre experience suggests that BMCS may be a safer alternative to the Wingspan stent for patients with symptomatic ICS who fail best medical therapy. Treatment of posterior circulation lesions was significantly more dangerous. Long term restenosis rates are low. Disclosures: A. Evans: None. S. Geraughty: None. J. Gaughen: None. L. Jensen: None. M. Wintermark: None.